Biogas technology in fuelwood saving and carbon emission reduction in southern Ethiopia - Desta, Getnet Alemu; Melka, Yoseph; Sime, Getachew; Yirga, Fikadu; Marie, Mequannt; Haile, Mebrahtu (Heliyon, 2020)
Most rural communities in developing countries, rely heavily on traditional biomass for cooking and lighting. Furthermore, a large area of forest land has been changed to other land-use types like agricultural land is becoming a serious problem in Wondo Genet district. This situation largely contributed to deforestation and forest degradation. Hence, assessing the efficiency of adopting an alternative source of energy was found to be very important. This study was carried out to examine the role of biogas technology in fuelwood saving and carbon emission reduction in Wondo Genet district, southern Ethiopia. The multi-stage sampling procedure was followed to select sample households. A total of 152 households (54 adopters and 98 non-adopters) were involved in the household survey. Moreover, 25 test subjects were taken randomly from both adoption categories to conduct Kitchen Performance Test. Descriptive statistics and independent-sample t-test were used to analyze the data. Results showed that the major fuel sources for domestic use were plantation forest, natural forest, crop residue, and animal dung, accounting 46.71 %, 30.92 %, 15.13 %, and 7.24 %, respectively. Among the 54 sampled biogas plants, 32 (59.26 %) were a digester size of 6 m3 whereas the remaining 22 (40.74 %) were of 8 m3. The annual fuelwood saving potential of the technology was found to be 1423.06 kg with an emission reduction potential of 2.1 tons of CO2 e per biogas plant annually. Accordingly, all functional biogas plants were estimated to reduce about 91.63 tons of carbon emission annually. Generally, the biogas was found to be a promising technology in combating the pressure on forest resources and mitigating climate change. Therefore, the energy sector of the country should encourage households to adopt biogas plants that have more than 8 m3 digester size to improve the fuelwood and carbon emission reduction potential. Adopter, biogas energy, deforestation, fuelwood, greenhouse gas emission.